(untitled) (Cultura Económica, 2018)
This article intends to carry out an essay observation on some networks as an object of concrete and particular study: Internet and the Web. Several outcomes from these networks put forward new ways of being and new means of human interaction, on such a scale that they drive a paradigm change in the way in which we live together. This phenomenon will be analysed within the framework of Philosophy of Technology to explain those new dynamics. Finally, this paper will seek to propose networks new vital environments whose cultural features are linked to a new revolution in the way we understand ourselves as human beings.